Uji Efektivitas Rizobakteria Dalam Menghambat Perkembangan Penyakit Hawar Pelepah Daun (Rhizoctonia solani Kuhn.) Pada Padi Secara In Vitro - Hanisa Desy Ariani; Noor Aidawati; Dewi Erika Adriani (Universitas Lambung Mangkurat, 2020)
One of the causes of the declining productivity of rice is sheath blight disease caused by the mold Rhizoctonia solani Kuhn. Control of sheath blight disease that is often done by the farmers is by using chemical pesticides (fungicides), which caused environmental problems. One way to reduce the use of pesticides is to biological control by using antagonist bacteria. This study aimed at in vitro test of rhizobacteria in preventing the development of sheath blight disease in rice plants. This research was conducted in the Phytopathology laboratory of Plant Protection Department of Faculty Agriculture, University of Lambung Mangkurat Banjarbaru from March to May 2018. The experiment used a randomized block design with three groups consisting of eight types of rhizobacteria isolates: (r1) Pseudomonas aeruginosa (Barito Kuala), (r2) Bacillus megaterium (Hulu Sungai Tengah), (r3) Azotobacter sp. (Barito Kuala), (r4) Pseudomonas sp. (Hulu Sungai Selatan), (r5) Flavobacterium sp. (Tanah Laut), (r6) Bacillus bodius (Barito Kuala), (r7) Pseudomonas aeruginosa (Hulu Sungai Selatan), (r8) Necercia sp. (Tanah Laut). The results showed that all rhizobacteria have the ability to inhibit the development of R. solani with different percentages of inhibitions. Pseudomonas aeruginosa (Barito Kuala) was the most effective rhizobacteria in inhibiting the development of R. solani.